Older Candidates for Subthalamic Deep Brain Stimulation in Parkinson's Disease Have a Higher Incidence of Psychiatric Serious Adverse Events - Cozac, Vitalii V.; Ehrensperger, Michael M.; Gschwandtner, Ute; Hatz, Florian; Meyer, Antonia; Monsch, Andreas U.; Schuepbach, Michael; Taub, Ethan; Fuhr, Peter (Frontiers in Aging Neuroscience, 2016)
Objective To investigate the incidence of serious adverse events (SAE) of subthalamic deep brain stimulation (STN-DBS) in elderly patients with Parkinson’s disease (PD). Methods We investigated a group of 26 patients with PD who underwent STN-DBS at mean age 63.2 ±3.3 years. The operated patients from the EARLYSTIM study (mean age 52.9 ±6.6) were used as a comparison group. Incidences of SAE were compared between these groups. Results A higher incidence of psychosis and hallucinations was found in these elderly patients compared to the younger patients in the EARLYSTIM study (p<0.01). Conclusions The higher incidence of STN-DBS-related psychiatric complications underscores the need for comprehensive psychiatric pre- and postoperative assessment in older DBS candidates. However, these psychiatric SAE were transient, and the benefits of DBS clearly outweighed its adverse effects.